A Novel Three-Component Reaction Involving Terminal Alkynes, Elemental Sulfur, and Strained Heterocycles - Samzadeh-Kermani, Alireza (Synlett, 2015)
An efficient one-pot procedure to synthesize 1,3-oxathiolane-2-alkylidene and 1,3-thiazolidine-2-alkylidene structures is described. Anionic adducts derived from terminal alkynes and elemental sulfur attack strained heterocycles regioselectively to afford the corresponding heterocyclic compounds.
Keywords: alkynes; epoxides; heterocycles; multicomponent reaction; sulfur; ring opening